PENGARUH WHISTLEBLOWING SYSTEM, KUALITAS AUDIT DAN KEBERAGAMAN GENDER DEWAN DIREKSI TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan BUMN yang Terdaftar di BEI Tahun 2015 – 2019) - Wahyu Kusumaningrum; Tarmizi Achmad (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of the whistleblowing system, audit quality and gender diversity of the board of directors on earnings management. Earnings management variable is used as the dependent variable, while the whistleblowing system, audit quality and gender diversity of the board of directors are used as independent variables, and use ROA, leverage ratio and firm size as control variables. The samples used in this study are state-owned companies listed on the Indonesia Stock Exchange with a total of 26 companies for 5 years. This study uses secondary data determined by the purposive sampling method and obtained from the company's official website or the Bloomberg laboratory. This study uses multiple linear regression analysis techniques. The results show that the whistleblowing system and the gender diversity of the board of directors have a negative effect on earnings management. This shows that the existence of a whistleblowing system and the presence of female directors in the company can limit the occurrence of earnings management practices. While audit quality has a positive effect on earnings management, which means that good audit quality is still not able to limit the occurrence of earnings management.